2017
DOI: 10.1001/jamaophthalmol.2016.5774
|View full text |Cite
|
Sign up to set email alerts
|

En Face Doppler Optical Coherence Tomography Measurement of Total Retinal Blood Flow in Diabetic Retinopathy and Diabetic Macular Edema

Abstract: to the New England Eye Center) from Carl Zeiss Meditec and Optovue and serving as a consultant to Regeneron and Genentech. Dr Baumal reports serving as a speaker for Allergan and Genetech, as well as having received compensations from Optovue. Dr Duker reports receiving grants from Carl Zeiss Meditec and Optovue while also serving as a consultant to Carl Zeiss Meditec and Optovue. Dr Duker also reports serving as a consultant to Allergan, Aura Biosciences, Lumenis, Omeros, Santen, Thrombogenics, and Ocudyne; b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…Studies on patients with diabetic retinopathy show slow and turbulent flow in areas of microaneurysms and vascular pruning, compared to the speed of flow in similar sized vessels without these alterations (Ishibazawa et al, 2016). Moreover, OCT based Doppler techniques suggest a reduction in total retinal blood flow in patients with diabetic macular edema, which is consistent with the extensive peripheral non-perfusion that is often seen on wide field imaging in these patients (Lee et al, 2017;Sadda et al, 2017a).…”
Section: Diabetic Macular Edemamentioning
confidence: 82%
“…Studies on patients with diabetic retinopathy show slow and turbulent flow in areas of microaneurysms and vascular pruning, compared to the speed of flow in similar sized vessels without these alterations (Ishibazawa et al, 2016). Moreover, OCT based Doppler techniques suggest a reduction in total retinal blood flow in patients with diabetic macular edema, which is consistent with the extensive peripheral non-perfusion that is often seen on wide field imaging in these patients (Lee et al, 2017;Sadda et al, 2017a).…”
Section: Diabetic Macular Edemamentioning
confidence: 82%
“…11,12 Several solutions were proposed to quantify total retinal blood flow (Q) based on Doppler optical coherence tomography (OCT). [13][14][15][16][17][18][19] Recently, a prototype instrument from a commercial company was introduced and good reproducibility was reported. 20 We have developed a technique based on a two-beam approach 15,[21][22][23] that has been validated against invasive microsphere technology in nonhuman primates.…”
mentioning
confidence: 99%
“…We also discovered that the PVD of the using group was lower than that of the without group, although it was a minimal difference. Previous studies reported a 1 0 decrease in pulsatile ocular blood flow was observed in the early stage of observable DR, and a lower PVD was related to the development and progression of DR. [33][34][35] A prior study reported that insulin could induce vascular endothelial production of nitric oxide, which leads to capillary recruitment, vasodilation, and increased blood flow. 36 However, our study demonstrated that insulin use could decrease the ocular PVD.…”
Section: Discussionmentioning
confidence: 99%